Исследование точности однокоординатного позиционирования промышленного робота-манипулятора - Криницын Н. С. Николай Станиславович; Бабаев А. С. Артём Сергеевич; Столов Е. В. Евгений Владимирович; Лаптев Н. В. Никита Витальевич; Пивкин П. М. Петр Михайлович; Хисамутдинов Р. М. Равиль Миргалимович (Робототехника, 2019)
Заглавие с экрана